Penalaran Arbiter: Standar Penilaian Bukti dalam Arbitrase Syariah - Audrey Naanthali Saputra; Anita Dewi; Sawitri Yuli Hartati S (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This research examines the evidentiary process in sharia arbitration, particularly within the National Sharia Arbitration Board (BASYARNAS), by employing a normative juridical approach. The study focuses on analyzing written legal norms and legal principles governing evidence in sharia arbitration, as regulated under Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, Law Number 21 of 2008 on Sharia Banking, and the BASYARNAS Procedural Rules. Primary legal materials consist of statutory regulations and relevant arbitration decisions, while secondary and tertiary materials include legal literature, academic journals, and legal dictionaries. The collected data are analyzed using descriptive-analytical methods and a comparative approach to identify differences between general arbitration and sharia arbitration evidentiary standards. The findings indicate that the evidentiary framework in sharia arbitration reflects flexibility and efficiency while adhering to sharia principles. Nevertheless, several challenges remain, particularly concerning the clarity of evidentiary standards and the adaptation to contemporary forms of evidence. Strengthening regulatory harmonization is therefore essential to enhance legal certainty and effectiveness in resolving sharia economic disputes through arbitration.